Multidrug-resistant and its coexistence with β-lactamases at a tertiary care hospital in a low-resource setting: a cross-sectional study with an association of risk factors - Pragyan Dahal; Mahendra Shrestha; Manisha Maharjan; Ranjana Parajuli (Therapeutic Advances in Infectious Disease)
Background: Pseudomonas aeruginosa is known to cause hospital-acquired infections. This bacterium produces β-lactamase enzymes that enzymatically degrade β-lactam drugs, reducing their efficacy. Objective: The objective of this investigation was to examine the occurrence, susceptibility, and production of various β-lactamases by multidrug-resistant P. aeruginosa (MDR-PA) and to determine the risk factors associated with extensively drug-resistant P. aeruginosa (XDR-PA) and their β-lactamases. Design: A descriptive cross-sectional study was conducted to investigate the occurrence, susceptibility, and β-lactamase production of MDR-PA and the risk factors associated with XDR-PA. The study involved collecting and analyzing 390 specimens from different 390 participants over a period from August 2021 to April 2023. Methods: The study utilized standard methodologies to screen and characterize P. aeruginosa . The antimicrobial-resistant patterns and presence of MDR-PA and XDR-PA were determined following standard guidelines supported by the Clinical Laboratory Standards Institute (CLSI) using various methods such as the disk diffusion method and colistin disk elution tests. Combined disk and inhibitor-based tests were used to determine extended-spectrum β-lactamases (ESBL), Metallo-β-lactamases (MBL), and AmpC-β-lactamases (AmpC) using two different methods. Clinical data were extracted from the medical records and patient requisition forms provided by clinicians. Clinical data were extracted for XDR-PA and β-lactamases applying binary logistic regression by adjusting for the confounding factors. Results: In our study, the antimicrobial-resistant pattern showed significant differences ( p  < 0.05) in the antibiotic-resistant pattern among β-lactamase and non-β-lactamase. The prevalence of MBL- P. aeruginosa was determined to be 13.5%, while ESBL accounted for 23.8%, and AmpC accounted for 20.5%. Coexistence of MBL + ESBL, ESBL + AmpC, MBL +  AmpC , and MBL + ESBL +  AmpC was determined to be 5.3%, 2.8%, 2.3%, and 4.1%, respectively. Among the nine assessed risk factors in a multivariate regression model, prolonged hospital stays (odd ratio = 11.2, 95% CI 3.7–33.8) provided substantial risk compared to other risk factors for the colonization of XDR-PA. Similarly, in a multivariate model, previous therapy with immunosuppressant drugs (OR = 6.7, 95% CI 1.5–29.3) was found to be the leading risk factor for the colonization of β-lactamase producers P. aeruginosa . Conclusion: Identification of XDR-PA and β-lactamases among MDR-PA isolates is crucial to prevent the use of unnecessary antibiotics. Early and prompt diagnosis of drug-resistant pathogens prevents treatment failure and encourages proper antibiotic therapy. Therefore, it is necessary to implement strict policies on the use of antibiotics without proper diagnosis.